A single-base resolution map of an archaeal transcriptome - Wurtzel, Omri; Sapra, Rajat; Chen, Feng; Zhu, Yiwen; Simmons, Blake A.; Sorek, Rotem (Genome Research, 2010)
Organisms of the third domain of life, the Archaea, share molecular characteristics both with Bacteria and Eukarya. These organisms attract scientific attention as research models for regulation and evolution of processes such as transcription, translation, and RNA processing. We have reconstructed the primary transcriptome of Sulfolobus solfataricus P2, one of the most widely studied model archaeal organisms. Analysis of 625 million bases of sequenced cDNAs yielded a single-base-pair resolution map of transcription start sites and operon structures for more than 1000 transcriptional units. The analysis led to the discovery of 310 expressed noncoding RNAs, with an extensive expression of overlapping cis-antisense transcripts to a level unprecedented in any bacteria or archaea but resembling that of eukaryotes. As opposed to bacterial transcripts, most Sulfolobus transcripts completely lack 5′-UTR sequences, suggesting that mRNA/ncRNA interactions differ between Bacteria and Archaea. The data also reveal internal hotspots for transcript cleavage linked to RNA degradation and predict sequence motifs that promote RNA destabilization. This study highlights transcriptome sequencing as a key tool for understanding the mechanisms and extent of RNA-based regulation in Bacteria and Archaea.